2005
DOI: 10.1111/j.1600-0501.2005.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

A distinguishable observation between survival and success rate outcome of hydroxyapatite‐coated implants in 5–10 years in function

Abstract: A distinguishable observation between survival and success rate was noted particularly in long-term observations. Implant length and diameter have an influence on the survival rate. Clinical parameter scores expressed an influence on the defined implant status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 62 publications
6
70
0
1
Order By: Relevance
“…These findings are in accordance with other investigators 28,30 who found a negative correlation between KM width and MR, and between KM width and GI. This study showed that implants with narrow zones of keratinized tissue (,2 mm) had significantly more plaque and signs of inflammation than those with wider zones of keratinized gingiva ($2 mm).…”
Section: Discussionsupporting
confidence: 95%
“…These findings are in accordance with other investigators 28,30 who found a negative correlation between KM width and MR, and between KM width and GI. This study showed that implants with narrow zones of keratinized tissue (,2 mm) had significantly more plaque and signs of inflammation than those with wider zones of keratinized gingiva ($2 mm).…”
Section: Discussionsupporting
confidence: 95%
“…Similarly, Baumgaertel and Hans 18 measured the buccal cortical plate thickness for mini-implant placement and found that it is more in the anterior mandible. Artzi et al 19 in their study evaluated the survival rate of 248 dental implants and found that the highest survival rate was seen in anterior mandible and the lowest in posterior maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…2,25,26 Surface character is one of the most important considerations for osseointegration. 27 Roughsurfaced implants showed higher success rates than machined smoothsurface implants, and higher removal torque was required for rough-surfaced implants than for machined smoothsurfaced implants. 28,29 Generally, short machined smooth-surfaced implants showed higher failure rates than long machined smooth-surfaced implants.…”
Section: Discussionmentioning
confidence: 97%